2019
DOI: 10.1016/j.heliyon.2019.e02741
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions for Mpt64 synthetic gene expression in Escherichia coli BL21 (DE3) using surface response methodology

Abstract: MPT64 is a specific protein that is secreted by Mycobacterium tuberculosis complex (MTBC). The objective of this study was to obtain optimum culture conditions for MPT64 synthetic gene expression in Escherichia coli BL21 (DE3) by response surface methodology (RSM). The RSM was undertaken to optimize the culture conditions under different cultivation conditions (medium concentration, induction time and inducer concentration), designed by the factorial Box-Bhenken using Minitab 17 statistical software. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
(28 reference statements)
2
19
0
1
Order By: Relevance
“…1 A–C). Similar findings have been reported in the literature 22 . Different silent mutations were examined at initial codons to minimize the reported translation-hindering stable secondary structures at 5′ of mRNA 27 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1 A–C). Similar findings have been reported in the literature 22 . Different silent mutations were examined at initial codons to minimize the reported translation-hindering stable secondary structures at 5′ of mRNA 27 .…”
Section: Discussionsupporting
confidence: 93%
“…E. coli has an ability to show growth in culture even at lag phase of growth 20 , 21 . We have previously reported the cloning, purification and characterization of endoglucanase from Clostridium thermocellum 22 . The present study describes our experiments for the scaling-up of fermentation conditions to improve the yield and quality of endoglucanase by exploiting various influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our result was in agreement with other work which reported that a pH increase could improve the level of Reteplase production in E. coli [ 25 ]. Avoiding cellular stresses such as the metabolic burden of acidification and proteases during the synthesis of recombinant proteins can contribute enormously to overall cell growth [ 10 ]. C source metabolism leads to the accumulation of acetate and acidic by-products in the culture medium that can reduce cell growth and recombinant protein production.…”
Section: Discussionmentioning
confidence: 99%
“…Several elements may control cell growth, such as Carbon (C) and Nitrogen (N) sources, metal ions, and the medium pH. Thus, it is essential to utilize the optimum culture composition to obtain a high yield of recombinant protein [ 10 ]. The number of contributing factors is high, and thus, it is a laborious and time-consuming task to examine the effect of each level of each variable one by one via the One-factor-at-a-time approach (OFAT).…”
Section: Introductionmentioning
confidence: 99%
“…It is 26-KD secreted mycobacterial protein [36,37]. Secreted mycobacterial proteins are involved in encouraging defensive immunity [38], and are considered immunodominant and but there are less evidences for the function of MPT64 in host immune capacity. This Ag induces T-cell responses in TB patients [39] and has been spotted in the macrophages of humanoid & mouse TB wounds [40,41].…”
Section: Mpt64mentioning
confidence: 99%